Arranjos produtivos locais: da teoria à prática: um estudo de caso do aglomerado produtivo de cerâmica estrutural do Município de Alagoinhas - Bahia - ARAÚJO, Ana Rita Motas (2015)
The objective of this study is to investigate whether the industries productive cluster of ceramics structural in the municipality of Alagoinhas, Bahia and its surroundings, meet the essential features in the literature that deals about Local Productive Arrangements (APL), to be considered as a cluster Industrial APL type. It uses the concept of Local Productive Arrangement, as a geographical concentration of companies of certain sector, including suppliers of inputs and services, which presents a variable degree of interaction between agents. In this study, it seek itself to know: if the economic literature says that, for a given industrial agglomeration be considered a cluster, it is necessary to consider jointly factors such as geographic location; interdependence; cooperation; competitiveness; dissemination of knowledge; innovation and trust, then it is possible to classify the set consists of five companies, operating in the productive sector of structural ceramics in the municipality of Alagoinhas, Bahia and its surroundings, as an APL or these firms do not meet features for classification as such? Productive clustering models are presented to explain the emergence and development of APL, seeking to validate the latter in the ceramic cluster of the municipality. The methodology applied to the research is qualitative and descriptive, because there is a small population of companies active in this sector. The origin of this crowded city, started in the 90s, has attributed to the existence of abundant clay deposits, the main raw material used in ceramic production, considered excellent quality. Despite being active in Alagoinhas market for more than ten years, little business interaction and the few links between companies and other Institutions such as universities and research centers, difficult actions that encourage greater local cooperation and the performance of these industries. It can be said that the cluster as APL found in embryonic or elementary stage, but with the possibility of advancing evidence to another stage, since there is still space for greater coordination between the actors, especially the intercompany joints because there is little initiative towards cooperation from entrepreneurs themselves. Overall, companies of APL in Alagoinhas ceramics structural, don’t realized the opportunities to act in a coordinated and nearby universities form; research centers and other local Institutions, aiming to reach a new standard that can be more performante, the sector in which they operate. Therefore, the research had identified that there is a need for the presence of an Institution, to play the role of a coordinating agent in this process.